2011
DOI: 10.1002/bmc.1652
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive method for the determination of JI‐101, a multi‐kinase inhibitor in human plasma and urine by LC‐MS/MS‐ESI: method validation and application to a clinical pharmacokinetic study

Abstract: A highly sensitive, rapid assay method has been developed and validated for the estimation of JI-101 in human plasma and urine using LC-MS/MS-ESI in the positive-ion mode. The assay procedure involves extraction of JI-101 and alfuzosin (internal standard, IS) from human plasma/urine with a solid-phase extraction process. Chromatographic resolution was achieved on two Zorbax SB-C(18) columns connected in series with a PEEK coupler using an isocratic mobile phase comprising acetonitrile-0.1% formic acid in water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The most abundant fragment ion was found at m / z 265, resulting from breakage of the amino ketone group. All publications have indicated same observations for the selection of ions for multiple reaction monitoring (Gurav et al ., , ; Sharma et al ., ).…”
Section: Detection Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…The most abundant fragment ion was found at m / z 265, resulting from breakage of the amino ketone group. All publications have indicated same observations for the selection of ions for multiple reaction monitoring (Gurav et al ., , ; Sharma et al ., ).…”
Section: Detection Methodsmentioning
confidence: 97%
“…() reported that, after acidification with 2% acetic acid, the samples were injected directly onto to the system; the recovery was found to be more than 70% compared with Sharma et al . (), where it was 50%.…”
Section: Sample Preparationmentioning
confidence: 94%
See 3 more Smart Citations